Human migrations, anthropogenic changes, and insect-borne diseases in Latin America - André B. B. Wilke; Priscilla Farina; Marco Ajelli; Angelo Canale; Filipe Dantas-Torres; Domenico Otranto; Giovanni Benelli (Parasites & Vectors)
Abstract Rapid urbanization and migration in Latin America have intensified exposure to insect-borne diseases. Malaria, Chagas disease, yellow fever, and leishmaniasis have historically afflicted the region, while dengue, chikungunya, and Zika have been described and expanded more recently. The increased presence of synanthropic vector species and spread into previously unaffected areas due to urbanization and climate warming have intensified pathogen transmission risks. This review examines recent outbreaks and reemergence of insect-borne diseases through five case studies: (i) malaria transmission linked to political instability and large-scale migration through the Amazon jungle; (ii) the expansion of triatomine bug habitats into overcrowded, substandard urban settlements, increasing Chagas disease incidence; (iii) the influence of movement and ecotourism in the Amazonia on yellow fever transmission in peri-urban areas; (iv) the spread of visceral leishmaniasis driven by deforestation and human–canine movement; and (v) dengue outbreaks in rural Amazon regions, spurred by urbanization and rural development. The findings underscore the complex interactions among vectors, pathogens, and shifting environmental and social conditions, complicating predictability and control. Addressing the social, economic, and political determinants of health is crucial to reducing disease transmission. Key measures include scaling vaccine coverage, especially for dengue and yellow fever; developing vaccines and treatments for neglected diseases; improving housing and sanitation; strengthening vector surveillance and control; fostering community engagement; enhancing data-driven interventions. Graphical Abstract